Experimental and Theoretical Data on the Mechanism by Which Red Wine Anthocyanins Are Transported through a Human MKN-28 Gastric Cell Model - Helder Oliveira (2015)
The gastric absorption of red wine anthocyanins was evaluated using a gastric MKN-28 cell barrier model. Anthocyanin transport was not affected by the presence of 4% ethanol and decreased with the increase of pH. Gastric cells pretreated with anthocyanins were found to increase anthocyanin transport. The presence of D-(+)-glucose was found to decrease anthocyanin uptake, suggesting the involvement of glucose transporters. RT-PCR assays revealed that GLUT1, GLUT3, and MCT1 transporters were expressed in MKN-28 cells. Computational studies were performed to provide a structural characterization of the binding site of hGLUT1 to glucose or different anthocyanins under different forms. Docking results demonstrated that anthocyanins can bind to glucose transporters from both intracellular and extracellular sides. Anthocyanins seem to enter into the transporter by two main conformations: B ring or glucose. From MD simulations, hGLUT1 was found to form complexes with all anthocyanins tested in the different protonation states.